2021
DOI: 10.1038/s41586-021-03905-5
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation landscape of biomolecular condensates

Abstract: Forming at the right place and time is important for all structures within living cells. This includes condensates such as the nucleolus, Cajal bodies, and stress granules, which form via liquid-liquid phase separation (LLPS) of biomolecules, particularly proteins enriched in intrinsically-disordered regions (IDRs) 1, 2 (Fig. 1a). In non-living systems, the initial stages of nucleated phase separation arise when thermal fluctuations overcome an energy barrier due to surface tension. This phenomenon can be mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
137
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(144 citation statements)
references
References 25 publications
7
137
0
Order By: Relevance
“…However, in more typical rapidly dividing mammalian cells, nuclear bodies, such as nucleoli and speckles 8,17 , tend to appear following mitosis and coalesce 18 , but then maintain relatively stable sizes until the next cell division, likely in part due to strong mechanical constraints from chromatin [19][20][21][22] . This picture is consistent with other recent work that has taken advantage of synthetic nuclear condensates, which form quickly 23 but grow and coalesce slowly due to their constrained, subdiffusive motion 20 .…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, in more typical rapidly dividing mammalian cells, nuclear bodies, such as nucleoli and speckles 8,17 , tend to appear following mitosis and coalesce 18 , but then maintain relatively stable sizes until the next cell division, likely in part due to strong mechanical constraints from chromatin [19][20][21][22] . This picture is consistent with other recent work that has taken advantage of synthetic nuclear condensates, which form quickly 23 but grow and coalesce slowly due to their constrained, subdiffusive motion 20 .…”
Section: Introductionsupporting
confidence: 92%
“…Here, we have shown that both native nuclear speckles and synthetic condensates form via a quench-then-coalesce mechanism, which may present a common mechanism for size control of condensates. Indeed, several native organelles within the nucleus, including nuclear speckles 8 but also nucleoli 23 , Cajal bodies 23 , histone locus bodies, paraspeckles, and PML bodies, all disassemble or scatter into the cytoplasm during mitosis 18 , likely due to a combination of dilution and post–translational modifications 19,41 , and then nucleate and regrow in the resulting daughter nuclei. Our results show that a relatively narrow, exponentially decaying size distribution will be attained for simple regrowth driven by coalescence.…”
Section: Discussionmentioning
confidence: 99%
“…Recent progresses in multiple loci (Zhou et al 2017) and in super-resolution (Alexander et al 2019;Chen et al 2018;BrandĂŁo et al 2020;Barth et al 2020) live imaging would make it possible to test quantitatively the relations between mobility, coherent motion and compaction predicted by our polymer models and the role of basic mechanisms such as phase separation or loop extrusion in regulating chromosome dynamics. For example, live-imaging the coupled structural and dynamical responses of chromatin after rapid in vivo perturbations of the amount of key chromatin-binding complexes using the auxin-inducible-degron system (Schwarzer et al 2017;Dobrinić et al 2021) or after modifications of their self-interacting capacities using optogenetics (Shin et al 2019;Shimobayashi et al 2021) would allow to directly investigate how chromatin dynamics respond to changes in chromatin compaction.…”
Section: Discussionmentioning
confidence: 99%
“…Above a critical radius a * , the free energy of cluster formation overcomes the interfacial penalty, and the new dense phase grows in a thermodynamically downhill fashion. Recently, these ideas from classical nucleation theory were applied to analyze and interpret the dynamics of phase separation in supersaturated solutions in cells (12, 13, 15).…”
Section: Introductionmentioning
confidence: 99%